A politics of the ordinary - Dumm, Thomas L. (New York University Press, 1999)
In A Politics of the Ordinary, Thomas Dumm dramatizes how everyday life in the United States intersects with and is influenced by the power of events, on the one hand, and forces of conformity and normalcy on the other. Combining poststructuralist analysis with a sympathetic reading of a strain of American thought that begins with Emerson and culminates in the work of Stanley Cavell, A Politics of the Ordinary investigates incidents from everyday life, political spectacles, and popular culture. Whether juxtaposing reflections about boredom in rural New Mexico with Emerson's theory of constitutional amendment, Richard Nixon's letter of resignation with Thoreau's writings to overcome quiet desperation, or demonstrating how Disney's Toy Story allegorizes the downsizing of the American white-collar work force, Dumm's constant concern is to show how the ordinary is the primary source of the democratic political imagination.